2021
DOI: 10.3390/ma14185360
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Porous Additive-Manufacturing Titanium Artificial Bone in Rat Calvarial Bone Defects

Abstract: Jaw reconstruction using an additive-manufacturing titanium artificial bone (AMTAB) has recently attracted considerable attention. The synthesis of a titanium artificial bone is based on three-dimensional computed tomography images acquired before surgery. A histological evaluation of porous AMTAB (pAMTAB) embedded in rat calvarial bone defects was conducted. This study examined three groups: rats implanted with mixed-acid and heat-treated pAMTAB, rats implanted with untreated pAMTAB, and rats with no implant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…On the contrary, Tanzer et al did not observe bone ingrowth at the porous-coated shoulder of explanted prostheses histologically but fibrous tissue was found which is also capable of providing additional stability [10,17]. Preclinical studies have shown that additive-manufactured titanium, as also used in the here studied 3D-printed collars, promotes novel bone formation and exhibits biomechanical properties comparable to cancellous bone [18][19][20].…”
Section: Discussionmentioning
confidence: 61%
“…On the contrary, Tanzer et al did not observe bone ingrowth at the porous-coated shoulder of explanted prostheses histologically but fibrous tissue was found which is also capable of providing additional stability [10,17]. Preclinical studies have shown that additive-manufactured titanium, as also used in the here studied 3D-printed collars, promotes novel bone formation and exhibits biomechanical properties comparable to cancellous bone [18][19][20].…”
Section: Discussionmentioning
confidence: 61%
“…With the advent of different biomaterials, bone and cartilage tissue engineering have received a lot of attention. The main goal of bone tissue engineering is to prepare a material that can be used for cellular remodeling by the body itself after artificial introduction of a bone defect [84]. Despite considerable progress in the development of biomaterials for bone tissue engineering applications, there are still some barriers to clinical translation.…”
Section: Bone and Cartilage Tissue Engineeringmentioning
confidence: 99%
“…However, the thickness of the skull bones has been evaluated in two-dimensional limited sections on the basis of computed tomography (CT) scan slices [10,11]. Another way to obtain thickness measurements is to create a three-dimensional (3D) model of the skull bone [12]. Modeling was performed on the basis of MRI data, which allowed the skull shape to be reconstructed, but this method also was not able to take into account the inner surface, and the skull thickness could not be evaluated at the desired level [13].…”
Section: Introductionmentioning
confidence: 99%